“Euro Sustainability”: Five Policy Proposals to Make the Euro Sustainable for the European Economy - Capuano, Giuseppe (Ekonomika, 2018)
The provided economic analysis and the economic policy proposed in this article are the natural verifications and continuations of a research that was started with the author’s described theory in Single Currency, Economic Development and Local Economies. A Critical Analysis of the Economic Policy of the Euro (1998). He emphasized the presence of important critical factors on the Economic and Monetary Union (EMU) which, if not solved, would undermine its existence; however, the importance of EMU’s policy was not questioned. This article offers a sustainability strategy of the Euro, called a “push investment approach,” which provides complementary public and private investment, strengthens the euro area governance and gradually eliminates the Maastricht criteria. Furthermore, the policy makes the Euro sustainable for all the acceding countries, constitutes development as well as the competitive factor and it is not critical to enterprises.
Keywords: Euro; governance; Maastricht criteria; EMU policy; sustainability